Serum Vitamin B12, Homocysteine and Methylmalonic Acid Levels in Patients With Parenchymal Neuro-Behçet’s Syndrome - Berivan BİTİK and Abdurrahman TUFAN and Şehri ELBEG and Rıdvan MERCAN and Hamit KÜÇÜK and Orhan KÜÇÜKŞAHİN and Mehmet Akif ÖZTÜRK and Seminur HAZNEDAROĞLU and Berna GÖKER (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the role of serum levels of vitamin B12 (VitB12), homocysteine (Hcy), and methylmalonic acid (MMA) in the development of parenchymal neuro-Behçet’s syndrome (NBS) and to compare them with healthy controls and Behçet’s syndrome (BS) patients without NBS. Patients and methods: Serum VitB12, Hcy, and MMA were measured using enzyme-linked immunosorbent assay in 64 patients (36 males, 28 females; mean age 36±8.3 years; range 20 to 56 years) who met the criteria of the International Study Group for Behçet’s Disease and 30 matched healthy controls (17 males, 13 females; mean age 35.76±9.6 years; range 20 to 50 years). The study participants were grouped as BS patients with NBS, BS patients without NBS, and healthy controls. Results: There was no significant difference between the groups regarding serum VitB12, Hcy, and MMA levels (p>0.05). Serum VitB12 levels were below the lower limit and serum Hcy levels were above the upper limit in all participants. MMA levels were normal in all participants. There was no correlation between the serum levels of VitB12, Hcy, and MMA and disease activity (p>0.05). Conclusion: The results of this study suggest that there is no significant association between VitB12 deficiency and parenchymal NBS. Further studies are needed to investigate the underlying mechanisms of the variable effects of VitB12 deficiency on different clinical manifestations of BS.